Tissue flossing: a new short-term compression therapy for reducing exercise-induced delayed-onset muscle soreness. A randomized, controlled and double-blind pilot crossover trial - Prill, R.; Schulz, R.; Michel, S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The symptomatic reduction of exercise-induced delayed-onset muscle soreness (DOMS) is of great interest in the fields of Sports Medicine and Physical Therapy. At this time, few therapeutic interventions have proven their effectiveness. One of the most promising interventions is compression therapy. The object of this study is tissue flossing, a therapeutic short-term compression method and whether its post-exercise application can reduce the extent of perceived DOMS. METHODS: Participants (N.=17) without any musculoskeletal injuries were recruited from university students. Participants performed an exercise protocol and obtained the intervention subsequently on one of both arms. Participants had to return for a second day to perform the whole procedure again, this time receiving the flossing intervention on the other arm. At both timepoints, their opposite arms served as the control. The primary outcome measure was a patient-reported score on a 100-mm Visual Analogue Scale. RESULTS: The mean value of DOMS of the flossed arm was 42 mm compared to the non-flossed arm was 48 mm. Differences were found to be statistically significant at 24 hours (P=0.036; a=0.05), as well as at 48 hours post-intervention (P=0.035; a=0.05). Effect sizes were dz=0.408 at 24 hours-and dz=0.411 at 48 hours post-intervention. The clean language effect size was 0.66. CONCLUSIONS: Tissue flossing appears to be an effective method for treating DOMS which is slightly less effective but much more practicable than gold standard treatment.